2017
DOI: 10.1155/2017/6017958
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Diagnosing Brain Death at an Academic Medical Center

Abstract: Objective. Research continues to highlight variability in hospital policy and documentation of brain death. The aim of our study was to characterize how strictly new guidelines of American Academy of Neurology (AAN) for death by neurological criteria were practiced in our hospital prior to appointment of neurointensivists. Method. This is a retrospective study of adults diagnosed as brain dead from 2011 to 2015. Descriptive statistics compared five categories: preclinical testing, neurological examination, apn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 23 publications
2
16
0
1
Order By: Relevance
“…Intracerebral hemorrhage was the most common cause of brain death in our study, similar to the studies by Escudero et al [13] and Pandey et al [3]. However, many studies reported different primary causes of brain death [14-15,19].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Intracerebral hemorrhage was the most common cause of brain death in our study, similar to the studies by Escudero et al [13] and Pandey et al [3]. However, many studies reported different primary causes of brain death [14-15,19].…”
Section: Discussionsupporting
confidence: 90%
“…In our hospital, 44.5% of brain death cases became donors between 2011 and 2016. Most of the patients diagnosed with brain death were male, similar to other studies [3,13-16]. Trauma is more common in males in some studies in our country, but there is no information about gender in the Turkish Statistical Institute data.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In Turkey two clinicians with specific departments are required to diagnose BD. There is a huge variability of knowledge and practices for BD declaration among physicians despite there are clear algorithms for the diagnosis (11)(12)(13). It was reported that asynchrony between physicians may cause problems not only in the diagnosis of BD but also organ donation.…”
Section: (42)mentioning
confidence: 99%